2007
DOI: 10.1002/lt.21050
|View full text |Cite
|
Sign up to set email alerts
|

Early indicators of prognosis in fulminant hepatic failure: An assessment of the Model for End-Stage Liver Disease (MELD) and King's College Hospital Criteria

Abstract: While King's Hospital Criteria (KCH) criteria are used worldwide, the Model for End-Stage Liver Disease (MELD) is a more recently developed scoring system that has been validated as an independent predictor of patient survival in conditions for liver transplantation (LT). The aim of the present study was to compare MELD and KCH criteria with other early clinical prognostic indicators (CPI) in a cohort of patients with fulminant hepatic failure (FHF). A total of 144 patients (mean age 31.7 Ϯ 14.7 yr; range 12-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
102
2
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(109 citation statements)
references
References 37 publications
3
102
2
2
Order By: Relevance
“…3 In fact, lactate alone at 12 hours had similar performance to SOFA and better performance than King's criteria (AUC: 0.76, 0.79, and 0.65, respectively). 3 Importantly, the negative predictive value (NPV), which is low in many prognostic scores in FHF, as acknowledge by Yantorno et al 2 in their discussion, was higher for lactate at 12 hours (NPV: 0.73), compared to the NPV of the King's criteria (NPV: 0.65) in our study, 3 and to the NPVs of the new prognostic score and MELD score (NPV: 0.65 and 0.61, respectively) in the study by Dhiman et al 1 Thus, we believe that further studies are needed to assess the prognostic accuracy of any new markers both early in the course of FHF and serially, as Dr. O'Grady 9 emphasized in the editorial accompanying the Dhiman et al 1 article. This should lead to better prognostication at different time points during the evolution of the FHF.…”
supporting
confidence: 48%
See 1 more Smart Citation
“…3 In fact, lactate alone at 12 hours had similar performance to SOFA and better performance than King's criteria (AUC: 0.76, 0.79, and 0.65, respectively). 3 Importantly, the negative predictive value (NPV), which is low in many prognostic scores in FHF, as acknowledge by Yantorno et al 2 in their discussion, was higher for lactate at 12 hours (NPV: 0.73), compared to the NPV of the King's criteria (NPV: 0.65) in our study, 3 and to the NPVs of the new prognostic score and MELD score (NPV: 0.65 and 0.61, respectively) in the study by Dhiman et al 1 Thus, we believe that further studies are needed to assess the prognostic accuracy of any new markers both early in the course of FHF and serially, as Dr. O'Grady 9 emphasized in the editorial accompanying the Dhiman et al 1 article. This should lead to better prognostication at different time points during the evolution of the FHF.…”
supporting
confidence: 48%
“…In addition, for the first time, we found that SOFA score at 48 hours postadmission is superior to SOFA score at admission in patients with acute complications of cirrhosis. 6 Dhiman et al 1 recognized that important survival factors, such as lactate, pH, phosphates, and ␣-fetoprotein, were not assessed in their study, as the data was collected retrospectively over almost 10 years. Currently, serum lactate is considered an established early prognostic marker of survival in patients with FHF.…”
mentioning
confidence: 99%
“…Numerous prognostic models have been proposed, notable among which are the King's College Hospital criteria 1 and model for end-stage liver disease (MELD) 2 and two such models from India by Acharya et al 3 and Dhiman et al 4 The existing prognostic models are based on admission parameters and do not take into account the dynamicity of the illness and hence have poor efficacy in predicting outcome in ALF.…”
Section: Commentmentioning
confidence: 99%
“…Patients from the study of Dhiman et al 2 exclusively had a viral etiology for FHF, whereas patients from the other study 1 had multifactorial causes. The etiology of FHF might be important because the King's College criteria have proposed different predictive variables for FHF with respect to the use or nonuse of acetaminophen.…”
mentioning
confidence: 95%
“…1,2 The two studies by Yantorno et al 1 from Argentina and Dhiman et al 2 from India investigated the prognostic ability of the Model for End-Stage Liver Disease (MELD), King's College, and Clichy criteria for predicting the mortality in patients with fulminant hepatic failure (FHF). Yantorno et al reported that MELD is the best prognostic model among the three, whereas Dhiman et al found that a combination of the parameters (clinical prognostic indicators) from these models is more accurate.…”
mentioning
confidence: 99%